انسداد الأمعاء الدقيقة: الأسباب والتدبير الجراحي - حاج قاسم فؤاد (Latakia University Journal -Medical Sciences Series, 2019)
تهدف هذه الدراسة الراجعة إلى تحري مسببات انسدادات الأمعاء الدقيقة و طرق التدبير في مشفى الأسد الجامعي في اللاذقية , شملت هذه الدراسة 71 مريضا،ً عولجت انسدادات الأمعاء الدقيقة لديهم جراحيًا وبشكل إسعافي. جرى تقسيم المرضى بحسب العمر والجنس إلى فئات عمرية كل منها 10 سنوات، وكان معدل إصابة الذكور ( 46 حالة) أعلى من معدل إصابة الإناث ( 25 حالة) ، و بلغت نسبة إصابة الذكور الضعف نسبة للإناث في الفئات العمرية الأكثر من 61 سنة, و كانت أكبر نسبة للإصابة بانسدادات الأمعاء الدقيقة تقع في الفئات العمرية بين 21 و 60 سنة. لقد شكلت الالتصاقات أكثر أسباب انسدادات الأمعاء الدقيقة شيوعًا (21 حالة 29.5 %)، تلتها اللجم 14حالة 19.7%، والفتوق الخارجية 10 حالات أي 14% . تم إجراء الاستئصال و المفاغرة البدئية مع استخدام الخياطة على طبقتين في 15 حالة ( 21.1 %)، وأجريت عمليات فك الالتصاقات في 19 حالة ( 26.7 %), وفك اللجم في 14 حالة ( 19.7 %), وتم تدبير بقية الحالات بإجراءات جراحية مختلفة. حدثت الوفاة في 3 حالات ( 4 %)، حدث انفكاك للمفاغرات لدى مريض واحد (1.4%)، ، ونزف عبر المفجرات في حالة واحدة )1.4%) . إن أهمية التشخيص الدقيق و السريع لانسداد الأمعاء الدقيقة تكمن في التقليل من خطورة المضاعفات القريبة والطويلة الأمد. This retrospective study aims to assess the causes of small bowels obstruction and their management during five years (2003-2008) at Al-Assad University Hospital in Latakia. This study included 71 patients treated surgically and urgently for small bowels obstruction. The patients were divided according to age and sex groups. Males (46 cases) were generally affected more than females (25 cases), and the proportion of the affected males were double that of females at the age group exceeding 61 years. We found that the main incidence of small bowels obstruction was noticed between the 21-60 years age groups. Adhesions were the most common cause of the obstruction (21 cases; 29.5%), followed by bands obstruction (14 cases; 19.7%), and external hernias (10 cases; 14%). Resection and primary anastomosis was carried out in two layers and without protecting the anastomosis in 15 cases (21.1%), adhesionlysis in 19 cases (26.7%), and deviscaus of fibrous bands in 14 cases (19.7%); the rest of the cases were dealt with by various surgical managements. 3 patients died (the mortality rate was 4%); there was one case of anastomotic leakage, and we encountered one case of bleeding discharge. Urgent surgical management of bowels obstruction and educating patients and medical staff involved in such cases is mandatory to avoid complications of late cases of bowels obstruction.